2004
DOI: 10.1128/jvi.78.12.6287-6296.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Nef Stimulates Human Immunodeficiency Virus Type 1 Replication in Primary T Cells by Enhancing Virion-Associated gp120 Levels: Coreceptor-Dependent Requirement for Nef in Viral Replication

Abstract: The Nef protein enhances human immunodeficiency virus type 1 (HIV-1) replication through an unknown mechanism. We and others have previously reported that efficient HIV-1 replication in activated primary CD4 ؉ T cells depends on the ability of Nef to downregulate CD4 from the cell surface. Here we demonstrate that Nef greatly enhances the infectivity of HIV-1 particles produced in primary T cells. Nef-defective HIV-1 particles contained significantly reduced quantities of gp120 on their surface; however, Nef d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 73 publications
2
28
1
Order By: Relevance
“…The various HIV and SIV Nef alleles enhanced X4 virus production by 1.7-to 7.8-fold (average Ϯ standard deviation [SD], 5.4-fold Ϯ 2.0-fold; n ϭ 15) and that of R5 HIV-1 by 3.6-to 23.1-fold (average Ϯ SD, 11.5-fold Ϯ 5.1-fold; n ϭ 15) compared to the respective nef mutant HIV-1 constructs. This result is in contrast with that of Lundquist and coworkers (38), who reported that Nef is not required for efficient replication of R5-tropic HIV-1 strains in primary CD4 ϩ T cells. This apparent contradiction might be due to differences in the culture systems and activation protocols.…”
Section: Vol 81 2007contrasting
confidence: 99%
“…The various HIV and SIV Nef alleles enhanced X4 virus production by 1.7-to 7.8-fold (average Ϯ standard deviation [SD], 5.4-fold Ϯ 2.0-fold; n ϭ 15) and that of R5 HIV-1 by 3.6-to 23.1-fold (average Ϯ SD, 11.5-fold Ϯ 5.1-fold; n ϭ 15) compared to the respective nef mutant HIV-1 constructs. This result is in contrast with that of Lundquist and coworkers (38), who reported that Nef is not required for efficient replication of R5-tropic HIV-1 strains in primary CD4 ϩ T cells. This apparent contradiction might be due to differences in the culture systems and activation protocols.…”
Section: Vol 81 2007contrasting
confidence: 99%
“…However, these effects were limited in time since functionally defective nef alleles were also found in individuals who have controlled disease progression up to at least 11 years of infection and have thereafter showed unequivocal signs of progression to HIV disease, defined here as LP. In this regard, a recent report showed that Nef is not required for efficient replication of viruses that use solely CCR5 for entry (44). In addition, evolution of either gp41 Env in macaques infected with SIV deleted of nef (2) or chemokine coreceptor use towards CXCR4 in individuals infected with nef-deleted HIV (34) has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative ELISA for gp120. gp120 levels on virions were determined by ELISA as previously described (43). Briefly, Immulon flat-bottom 96-well plates (Dynex) were coated with gp120-specific sheep polyclonal antibody (4 g/ml; Cliniqa Inc.) for at least 6 h. Individual wells were blocked with 5% donor calf serum in PBS for 1 h, following washes.…”
Section: Methodsmentioning
confidence: 99%